In-silico approach towards thiophene incorporated 1,3-oxazepine using 5-HTT and 5-HT2AR receptors for antidepressant activity - Abhishek Kumar, Pankaj Kumar, S. Suhasini, P. Chaithanya, Gupta Dheeraj Rajesh, Suresh Suhasini, Periyadka Chaithanya (Journal of Applied Pharmaceutical Science, 2023)
Depression is a medical condition that affects a person’s mood and can be serious if it persists for a long time and is accompanied by other symptoms. The serotonin receptor family includes Serotonin transporter (or 5-HTT) and 5-HT2A, which are involved in the transportation of serotonin across the synaptic cleft. Schrödinger software was used to study how well novel thiophene-incorporated oxazepines could bind to these receptors. The ligand molecules TOB3, TOB13, and TOA13 had better docking scores against the protein 5-HTT than the standard Imipramine, while the docking scores of other compounds varied. The ligand TOA11 also had a good score against the 5-HT2AR protein. The results were validated using binding free energy analysis, pharmacophore modeling, and molecular dynamic simulation studies used to identify potent molecules for further study. Absorption, distribution, metabolism, excretion, and toxicity and physicochemical parameters were also predicted, and drug-likeness was evaluated. This study could aid in the development of potent inhibitors of 5-HTT and 5-HT2AR for the treatment of depression.
Keywords: Thiophene, oxazepine, antidepressant, SERT, 5-HT2A, in silico